Singapore : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
The economic downturns and an ongoing industrial restructuring toward capital-intensive sectors, such as chemical and pharmaceuticals, have contributed to rising unemployment. With the economic recovery continuing to gain momentum, the near-term outlook has improved. With broad agreement on the assessment of the economic outlook, the discussions focused on the appropriate policy stance and on structural reforms needed to raise Singapore's medium-term growth potential. The authorities are encouraged to develop and publish fiscal accounts, and to provide more information on the government's investment income.